Household crowding can have political effects: An empirical study on support for anti-democratic political systems during the COVID-19 lockdown in Italy. (August 2021) - Cavazza, Nicoletta; Russo, Silvia; Colloca, Pasquale; Roccato, Michele
Abstract: We analysed some political consequences of household crowding during the 2020 COVID-19 lockdown across a wide quota sample of the Italian adult population, stratified as concerns gender, age, level of education, geographical area of residence, and size of area of residence, interviewed before (May–June 2019) and during (April 2020) the lockdown ( N  = 1, 047, 51.2% women, M age  = 50.44, SD  = 14.36). Path analysis showed that household crowding during the lockdown was positively associated with support for anti-democratic political systems, through the partial mediation of the perceived relative impact of COVID-19 on one's family and of expectations of future lifestyle restrictions due to the pandemic. These associations did not depend on participants' pre-pandemic socio-economic status and predisposition to strong political leaders. Strengths, limitations, and possible developments of the study are discussed. Highlights: COVID-19 lockdown measures forced people to stay indoors 24/7. Household crowding during lockdown is associated with anti-democratic attitudes. Lifestyle restrictions and the impact of COVID-19 partially explain this link. This study shows relevant socio-political consequences of household density.